Study of Physiology and Some Biochemical Parameters in Infected People - Eman Hassan Salem Saloum; Mustafa Abdul-Hussein Salem Dasher; Fatima Turki Abdul Hussein Ajja; Taher Jameel Abdullah Mohammed; Layla Rateb Lafteh Aizan (Genius Journals, 2024)
This study was conducted in the laboratories of Al-Hakim Hospital Artificial Kidney Department in Najaf Governorate for the period from 1/2/2024 to 4/10/2024 with the aim of finding the relationship between some biochemical parameters and kidney disease in affected males. Blood samples were examined for (30) male patients entering the above-mentioned department who suffer from incapacitating kidney disease. The results were compared with the control group, which included (30) healthy males. After conducting the necessary tests, the following was found . : A study of one of the physiological blood parameters showed a significant decrease (P <0.05) in the hemoglobin concentration rate when compared with the control group . The study of blood biochemical parameters showed a significant decrease (P><0.05) in the concentration of calcium ions when compared with the control group, while the results showed a significant increase (P><0.05) in the concentration of sodium ions, potassium, creatine and urea compared with the control group. .Based on the results of this study, we can conclude that kidney disease negatively affected the biochemical parameters under study>
Keywords: Biochemical Parameters; Infected People; Physiology